MomL inhibits bacterial antibiotic resistance through the starvation stringent response pathway. Issue 4 (24th March 2022) - Dou, Qin; Yuan, Jin; Yu, Rilei; Yang, Jiahui; Wang, Jiayi; Zhu, Yuxiang; Zhong, Jing; Long, Hongan; Liu, Zhiqing; Wang, Xianghong; Li, Yuying; Xiao, Yichen; et al.
Abstract: Antibiotic resistance in gram‐negative pathogens has become one of the most serious global public health threats. The role of the N ‐acyl homoserine lactone (AHL)‐mediated signaling pathway, which is widespread in gram‐negative bacteria, in the bacterial resistance process should be studied in depth. Here, we report a degrading enzyme of AHLs, MomL, that inhibits the antibiotic resistance of Pseudomonas aeruginosa through a novel mechanism. The MomL‐mediated reactivation of kanamycin is highly associated with the relA ‐mediated starvation stringent response. The degradation of AHLs by MomL results in the inability of LasR to activate relA, which, in turn, stops the activation of downstream rpoS . Further results show that rpoS directly regulates the type VI secretion system H2‐T6SS. Under MomL treatment, inactivated RpoS fails to regulate H2‐T6SS; therefore, the expression of effector phospholipase A is reduced, and the adaptability of bacteria to antibiotics is weakened. MomL in combination with kanamycin is effective against a wide range of gram‐negative pathogenic bacteria. Therefore, this study reports a MomL‐antibiotic treatment strategy on antibiotic‐resistant bacteria and reveals its mechanism of action. Impact statement: To address the gradual ineffectiveness of new antibiotics, it is critical to highlight the effect of traditional antibiotics. Reducing or eliminating bacterial resistance by interfering with signaling pathways provides a possible solution to this problem. Our study reports a novel antibacterial strategy, MomL‐kanamycin treatment, in which MomL weakens antibiotic resistance by inhibiting the inner N ‐acyl homoserine lactone (AHL) signaling pathway. The applicability of our treatment strategy was proven in a series of AHL‐regulated gram‐negative bacteria. Our study provides positive evidence for the feasibility of an anti‐infective strategy based on bacterial signaling pathways.